Enhanced anaerobic fermentation of waste activated sludge by NaCl assistant hydrolysis strategy: Improved bio-production of short-chain fatty acids and feasibility of NaCl reuse. (September 2020) - Pang, Heliang; Xu, Jie; He, Junguo; Pan, Xinlei; Ma, Yingqun; Li, Le; Li, Kunyi; Yan, Zhongsen; Nan, Jun
Graphical abstract: Highlights: Additional NaCl triggered sludge disintegration with EPS disruption and cell lysis. More than 85% of SCOD was composed of proteins, carbohydrates and SCFAs. SCFAs yield reached 288.2 mg COD/g VSS after 4-day anaerobic fermentation. Mechanism based on osmotic pressure attack was proposed for sludge hydrolysis. Acetic and propionic acids accounted for more than 60% of the produced SCFAs. Abstract: This study developed an economical approach for enhancing short-chain fatty acids (SCFAs) production from waste activated sludge (WAS) by NaCl assistant anaerobic fermentation. With NaCl addition at 20 g/L, sludge disintegration with extracellular polymeric substance (EPS) disruption and cell lysis were induced owing to the attack of osmotic pressure, which facilitated WAS solubilization with release of biodegradable organic matters. The SCOD sharply increased to 4092 mg/L (SCOD/TCOD = 23.9%) after 2-day hydrolysis, against 1462 mg/L in the control. After 4-day anaerobic fermentation, considerable SCFAs production of 288.2 mg COD/g VSS was achievable. More than 60% of the SCFAs was composed of acetic and propionic acids. The feasibility of bio-electrogenesis in microbial fuel cell (MFC) utilizing fermentative liquid was assessed. As such, the produced SCFAs could be consumed with energy recovery, thereby the used NaCl was reusable, which created environmental and economic benefits, e.g. reduced NaCl consumption and cost, negligible residual NaCl.